If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -1i)(x + -1iy) = 3 + -11i Reorder the terms: (3 + -1i)(-1iy + x) = 3 + -11i Multiply (3 + -1i) * (-1iy + x) (3(-1iy + x) + -1i * (-1iy + x)) = 3 + -11i ((-1iy * 3 + x * 3) + -1i * (-1iy + x)) = 3 + -11i ((-3iy + 3x) + -1i * (-1iy + x)) = 3 + -11i (-3iy + 3x + (-1iy * -1i + x * -1i)) = 3 + -11i Reorder the terms: (-3iy + 3x + (-1ix + 1i2y)) = 3 + -11i (-3iy + 3x + (-1ix + 1i2y)) = 3 + -11i Reorder the terms: (-1ix + -3iy + 1i2y + 3x) = 3 + -11i (-1ix + -3iy + 1i2y + 3x) = 3 + -11i Solving -1ix + -3iy + 1i2y + 3x = 3 + -11i Solving for variable 'i'. Reorder the terms: -3 + 11i + -1ix + -3iy + 1i2y + 3x = 3 + -11i + -3 + 11i Reorder the terms: -3 + 11i + -1ix + -3iy + 1i2y + 3x = 3 + -3 + -11i + 11i Combine like terms: 3 + -3 = 0 -3 + 11i + -1ix + -3iy + 1i2y + 3x = 0 + -11i + 11i -3 + 11i + -1ix + -3iy + 1i2y + 3x = -11i + 11i Combine like terms: -11i + 11i = 0 -3 + 11i + -1ix + -3iy + 1i2y + 3x = 0 The solution to this equation could not be determined.
| x+y=1.70 | | 12(x-4)-8(2x-7)=3(x+5) | | 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 | | -5(-5z)=150 | | 4n+3=86 | | -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) |